1996
DOI: 10.1021/es9506364
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Level and Form of Chlorine on the Formation of Chlorinated Dioxins, Dibenzofurans, and Benzenes during Combustion of an Artificial Fuel in a Laboratory Reactor

Abstract: The formation of polychlorinated dibenzo-p-dioxins (PCDDs), dibenzofurans (PCDFs), and chlorobenzenes (PCBzs) in the combustion process was studied where the chlorine level and source were varied in an artificial waste. Different levels of organic chlorine (PVC) and inorganic chlorine (CaCl 2 ‚6H 2 O) were added to the fuel. The flue gas samples were analyzed for PCDDs/PCDFs and PCBzs. The following combustion parameters were measured during incineration: temperature in bed, in freeboard, and in cooling convec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 31 publications
4
36
0
Order By: Relevance
“…Thus in conditions of low Cl, the rate may be controlled by oxygen availability, but under excess Cl it may be proportional to the concentration of free chlorine. This is consistent with an apparent critical chlorine content in the fuel of 1 wt%, as found by Wikström et al [130]. Below this value, the chlorine content had no influence on the level of PCDD/F emissions, but above this value they rose.…”
Section: Chlorinesupporting
confidence: 91%
See 1 more Smart Citation
“…Thus in conditions of low Cl, the rate may be controlled by oxygen availability, but under excess Cl it may be proportional to the concentration of free chlorine. This is consistent with an apparent critical chlorine content in the fuel of 1 wt%, as found by Wikström et al [130]. Below this value, the chlorine content had no influence on the level of PCDD/F emissions, but above this value they rose.…”
Section: Chlorinesupporting
confidence: 91%
“…The concentration of HCl in the gas phase was found to be proportional to the quantity of chlorine added (as PVC) to the feed of both a lab furnace [129] and a 220 kg h −1 incinerator [63]. In the pilot incinerator at Umeå, no distinction was found [130] between the types of chlorine, i.e., organic (PVC) or inorganic (CaCl 2 ·6H 2 O) added to synthetic MSW. There was no correlation between the amounts of PCDD/F and PCBz formed and the chlorine content of the feed until the chlorine content approached 1 wt%.…”
Section: Chlorinementioning
confidence: 99%
“…As described previously, characteristics of feed waste is one of the factors influencing the formation of PCDDs/Fs during MSW incineration. Up to now, many studies on the effect of the total chlorine content in the waste on the formation of PCDDs/Fs have been conducted [8,15]. Some studies found a correlation while others did not [15], but recent research has tended to recognize the correlation between chlorine content in the waste and the formation of PCDDs/Fs [8].…”
Section: Pcdds/fs In Flue Gas Before Apcdmentioning
confidence: 99%
“…There are many papers in which PCDD/F formation from combustion of PVC alone or the influence of PVC as a chlorine source in MSW incinerators have been studied, as in [31][32][33]. Results obtained are sometimes difficult to compare because of the variety of operating conditions and systems used.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%